Modeling of Heat Exchange with Developed Nucleate Boiling on Tenons - A. V. Ovsiannik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper proposes a thermal and physical model for heat exchange processes with developed nucleate boiling on the developed surfaces (tenons) with various contours of heat transfer surface. Dependences for calculating convective heat exchange factor have been obtained on the basis of modeling representation. Investigations have shown that an intensity of convective heat exchange does not depend on tenon profile when boiling takes place on the tenons. The intensity is determined by operating conditions, thermal and physical properties of liquid, internal characteristics of boiling processes and geometrical characteristics of a tenon.